SXDF-UDS-CANDELS-ALMA 1.5 arcmin2 deep survey. Issue Volume 11:Issue S319(2015) (17th August 2016) - Kohno, K.; Yamaguchi, Y.; Tamura, Y.; Tadaki, K.; Hatsukade, B.; Ikarashi, S.; Caputi, K.I.; Rujopakarn, W.; Ivison, R.J.; Dunlop, J.S.; Motohara, K.; Umehata, H.; et al.
Abstract: We have conducted 1.1 mm ALMA observations of a contiguous 105" × 50" or 1.5 arcmin 2 window in the SXDF-UDS-CANDELS. We achieved a 5σ sensitivity of 0.28 mJy, giving a flat sensus of dusty star-forming galaxies with L IR 6×10 11 L ⊙ (if T dust =40K) up to z 10 thanks to the negative K-correction at this wavelength. We detected 5 brightest sources (S/N>6) and 18 low-significant sources (5>S/N>4; they may contain spurious detections, though). One of the 5 brightest ALMA sources ( S 1.1mm = 0.84 ± 0.09 mJy) is extremely faint in the WFC3 and VLT/HAWK-I images, demonstrating that a contiguous ALMA imaging survey uncovers a faint dust-obscured population invisible in the deep optical/near-infrared surveys. We find a possible [CII]-line emitter at z =5.955 or a low- z CO emitting galaxy within the field, allowing us to constrain the [CII] and/or CO luminosity functions across the history of the universe.